2009
DOI: 10.1038/emboj.2009.189
|View full text |Cite
|
Sign up to set email alerts
|

A conserved haem redox and trafficking pathway for cofactor attachment

Abstract: A pathway for cytochrome c maturation (Ccm) in bacteria, archaea and eukaryotes (mitochondria) requires the genes encoding eight membrane proteins (CcmABCDEFGH). The CcmABCDE proteins are proposed to traffic haem to the cytochrome c synthetase (CcmF/H) for covalent attachment to cytochrome c by unknown mechanisms. For the first time, we purify pathway complexes with trapped haem to elucidate the molecular mechanisms of haem binding, trafficking and redox control. We discovered an early step in trafficking that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
175
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(184 citation statements)
references
References 48 publications
8
175
0
Order By: Relevance
“…its covalent attachment to apocytochrome c (51,52). In Gramnegative bacteria, the cytochrome c synthetase CcmF was proposed to function as a quinol:heme oxidoreductase (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…its covalent attachment to apocytochrome c (51,52). In Gramnegative bacteria, the cytochrome c synthetase CcmF was proposed to function as a quinol:heme oxidoreductase (52).…”
Section: Discussionmentioning
confidence: 99%
“…In Gramnegative bacteria, the cytochrome c synthetase CcmF was proposed to function as a quinol:heme oxidoreductase (52). In addition, the lipocalin ␣1-microglobulin has the ability to reduce hemin in cytochrome c and methemoglobin (53).…”
Section: Discussionmentioning
confidence: 99%
“…This complex contained oxidized heme (Fe 3ϩ ) covalently bound to the His residue of CcmE, with CcmC providing two additional His residues as axial ligands of the heme iron (11).…”
mentioning
confidence: 99%
“…CcmF is a large multispan membrane protein with a b-type heme (11) and belongs to the heme handling protein (HHP) family like CcmC (supplemental Table S1) (14). Recently, it has been suggested that CcmF reduces the heme of holoCcmE to facilitate its transfer to the apocytochrome c (11,15). In ␣-proteobacteria (e.g.…”
mentioning
confidence: 99%
“…1). CcmF contains heme b and belongs to the heme handling protein family (8,9). It has a conserved periplasmic WWD motif and two conserved His residues that are proposed to acquire heme from holoCcmE (9).…”
mentioning
confidence: 99%